2002
DOI: 10.1088/0957-0233/14/1/305
|View full text |Cite
|
Sign up to set email alerts
|

Self-recalibration of a colour-encoded light system for automated three-dimensional measurements

Abstract: Colour-encoded structured lighting systems are widely used for three-dimensional data acquisition based on machine vision. Calibration of such a system is a laborious and tedious task. This paper presents a novel method for self-recalibration of such a vision system. The relative pose between the projector and camera of the system is automatically determined by taking a single view of the scene, so that the three-dimensional measurements and reconstruction can be performed efficiently even if it is moved from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Equation (5) shows that an accurate measurement result is depending on the four factors: (1) Accurate determination of the pixel coordinates on camera's image plane; 2) Unbiased camera's parameters; 3) Unbiased projector's parameters; 4) Accurate determination of the pixel point on the projector's image plane which corresponds to the pixel point on the camera's image plane. The first two conditions are easy to be satisfied with accurate camera calibration algorithm [1][2][3][4] and well-developed image processing technique [5]. However, the latter two aspects are much more difficult to be achieved.…”
Section: B Triangulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (5) shows that an accurate measurement result is depending on the four factors: (1) Accurate determination of the pixel coordinates on camera's image plane; 2) Unbiased camera's parameters; 3) Unbiased projector's parameters; 4) Accurate determination of the pixel point on the projector's image plane which corresponds to the pixel point on the camera's image plane. The first two conditions are easy to be satisfied with accurate camera calibration algorithm [1][2][3][4] and well-developed image processing technique [5]. However, the latter two aspects are much more difficult to be achieved.…”
Section: B Triangulationmentioning
confidence: 99%
“…In this process, the key to accurate reconstruction of an object's surface is proper calibration of each optical devices [5]. Many camera calibration methods are available to be utilized [1][2][3][4]. However, for projector calibration, even with the latest accurate calibration methods using active target and phase-shifting technique [3][5] [7] [10], the accuracy of projector calibration can hardly reach as the same level as the camera [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…A color block pattern is projected into dye-imbued water by the PC projector, and the surface of the water is recorded by the digital camera using an experimental setup similar to that of Chen and Li (2003). Three-dimensional surface shapes are estimated on the basis of the recorded relative locations of the block projections on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, the search algorithm converged to the global optimum solution within several seconds. This suggests the presence of a single global minimum of the error function 4 . As a test of robustness, we added uniform random noise (up to 5% of the simulated values) and found that the errors in recovered unknowns were low, as evidenced by the error histograms in figure 10.…”
Section: Scene and Medium Recoverymentioning
confidence: 94%
“…However, very few techniques explicitly analyze the influence of scattering on the appearances of scenes under active illumination 1 . Structured lighting is also widely used in computer vision, for 3D reconstruction of scenes [25], [14], [4], [11], [27], [19], [20]. However, an implicit assumption made in most methods is that light is neither scattered nor absorbed by the medium in which the scene and sources are immersed (as in pure air).…”
Section: Introductionmentioning
confidence: 99%